Proof of lung muscarinic receptor occupancy by tiotropium: Translational Positron Emission Tomography studies in non-human primates and humans - Cselényi, Zsolt; Jucaite, Aurelija; Ewing, Pär; Stenkrona, Per; Kristensson, Cecilia; Johnström, Peter; Schou, Magnus; Bolin, Martin; Halldin, Christer; Larsson, Bengt; Grime, Ken; Eriksson, Ulf G; et al. (Frontiers in Nuclear Medicine, 2023)
Molecular imaging has not been used to support the development of drugs for the treatment of pulmonary disorders. The aim of the present translational study was to advance quantitative pulmonary PET imaging by demonstrating occupancy of the reference asthma drug tiotropium at muscarinic acetylcholine receptors (mAChR). PET imaging was performed using the muscarinic radioligand [11C]VC-002. The key methodological step involved estimating muscarinic receptor binding while disentangling it from the background of non-specific binding. The relationship between tiotropium exposure and receptor occupancy (RO) was assessed in non-human primates (NHPs) after intravenous injection of tiotropium doses at a broad dose interval (0.03-1µg/kg). The feasibility of measuring RO in the human lung was then confirmed in seven healthy human subjects after inhalation of a single therapeutic dose of tiotropium (18µg). There was an evident effect of tiotropium on [11C]VC-002 binding to mAChRs in lungs in both NHPs and humans. In NHPs, RO was 11 to 78% and increased in a dose dependent manner. Non-displaceable binding in NHPs was about 10% of total binding. In humans, RO was 6-65%, and non-displaceable binding was about 20% of total binding at baseline. The results demonstrate that [11C]VC-002 binds specifically to mAChRs in the lungs enabling the assessment of RO following administration of muscarinic antagonist drugs. Furthermore, the methodology has potential not only for dose finding and comparison of drug formulations in future applied studies, but also for evaluating changes in lung receptor distribution during disease or in response to therapy.